ANALISIS PERBANDINGAN PAJAK BUMI DAN BANGUNAN SEBELUM DAN SETELAH PENGALIHAN MENJADI PAJAK DAERAH DI KELURAHAN YANG ADA DI KOTA PEKANBARU - Maulydia, Shavira; Basri, Yessi Mutia; Wiguna, Meilda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aims to determine whether there is a difference from the target of property tax, revenues realization of property tax, receivables of property tax, the object of property tax, and ease of paying property tax before and after transfer into a local tax.Population in this reaserch are 58 villages in the Pekanbaru city. This reaserch uses primary and secondary data. Sample selection technique used is saturated and sampling techniques. The analytica lmethodused is Wilcoxon Match Pair Testwith SPSS. Result of this study prove that there is not a difference between the target of property taxes before and after transfer. And there are significant difference between revenues realization of property tax, receivables of property tax, the object of property tax, and ease of paying property tax after transfer into a local tax.Keywords:target, revenues realization, tax,property tax, and tax object.